2010
DOI: 10.1089/vim.2009.0088
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Small Intestinal Epithelial Cell Line (IPEC-J2) of Rotavirus Infection As a New Model for the Study of Innate Immune Responses to Rotaviruses and Probiotics

Abstract: Previous studies of epithelial immune responses to rotavirus infection have been conducted in transformed cell lines. In this study, we evaluated a non-transformed porcine jejunum epithelial cell line (IPEC-J2) as an in-vitro model of rotavirus infection and probiotic treatment. Cell-culture-adapted porcine rotavirus (PRV) OSU strain, or human rotavirus (HRV) Wa strain, along with Lactobacillus acidophilus (LA) or Lactobacillus rhamnosus GG (LGG) were used to inoculate IPEC-J2 cells. LA or LGG treatment was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
126
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(135 citation statements)
references
References 70 publications
(105 reference statements)
8
126
0
1
Order By: Relevance
“…The supernatants were then divided into aliquots and stored at ÏȘ20°C. Virus antigens in the fecal swabs were detected by enzyme-linked immunosorbent assay (ELISA) (18). Rectal swabs from mock treatment Gn pigs were used as negative controls.…”
Section: Methodsmentioning
confidence: 99%
“…The supernatants were then divided into aliquots and stored at ÏȘ20°C. Virus antigens in the fecal swabs were detected by enzyme-linked immunosorbent assay (ELISA) (18). Rectal swabs from mock treatment Gn pigs were used as negative controls.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a cell line from jejunum epithelium isolated from a neonatal unsuckled piglet, small intestinal porcine epithelial cell line (IPEC-J2; Berschneider 1989) was characterized and used as an in vitro model system for studying porcine intestinal pathogen-host interactions, porcine-specific pathogenesis, and innate immune responses (Schierack et al 2006;Botic et al 2007;Brown and Price 2007;Skjolaas et al 2007;Koh et al 2008;Arce et al 2010;Liu et al 2010). This cell line, a non-transformed, nontumorigenic small intestinal cell line, can secrete mucin, produce cytokines/chemokines, and express Toll-like receptors similar to those of the original tissue.…”
Section: Introductionmentioning
confidence: 99%
“…IPEC-J2 cells, a cell line from jejunum epithelium isolated from a neonatal, unsuckled piglet (Berschneider, 1989), is an optimal model to study immune response in vitro. Previous studies have shown that inflammatory cytokines could be upregulated in IPEC-J2 cells exposed to LPS (Arce, Ramirez-Boo, Lucena, & Garrido, 2010), pathogenic bacteria (Geens & Niewold, 2010) and virus (Liu, Li, Wen, et al, 2010).…”
Section: Introductionmentioning
confidence: 99%